1995
DOI: 10.1007/bf00409410
|View full text |Cite
|
Sign up to set email alerts
|

Poor prognosis of severe chemical and thermal eye burns: the need for adequate emergency care and primary prevention

Abstract: The epidemiology and wound healing following medical and surgical treatment of 101 patients with 131 severely burnt eyes due to chemical or thermal agents have been analyzed. Most of the accidents occurred at work (72.3%); the majority of the burns were chemical (84.2%), of which 79.8% were caused by alkalis. The long average duration of treatment on ward (5.2 +/- 4.1 months) and the high number of surgical interventions (8.0 +/- 8.0) indicate the difficulties in treatment and the delayed recovery of the affec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
33
0
1

Year Published

2005
2005
2022
2022

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 62 publications
(38 citation statements)
references
References 12 publications
2
33
0
1
Order By: Relevance
“…The expressions of eye irritation and eye burns define a variety of interactions of chemical fluids, powders, and foreign bodies when they interfere with the ocular surface [7]. In this chapter, we shall focus on the mechanistic understanding of the known facts in this field.…”
Section: Types Of Burns and Eye Irritationmentioning
confidence: 99%
“…The expressions of eye irritation and eye burns define a variety of interactions of chemical fluids, powders, and foreign bodies when they interfere with the ocular surface [7]. In this chapter, we shall focus on the mechanistic understanding of the known facts in this field.…”
Section: Types Of Burns and Eye Irritationmentioning
confidence: 99%
“…Alkali-induced eye burns require long-term treatment [29]. Despite the maximal medical efforts, in some cases it is impossible to achieve rehabilitation [11]. This study tries to qualify and quantify the effects and importance of immediate emergency rinsing of the eye.…”
Section: Introductionmentioning
confidence: 99%
“…Kuckelkorn et al [13] reported that the visual prognosis for chemically injured eyes that received immediate irrigation was significantly improved. In the present study, immediate copious irrigation with tap water also reduced the severity in alkali burns and improved the healing time of the injured eyes.…”
Section: Discussionmentioning
confidence: 99%
“…Chemical injuries of the eye have produced extensive damage in many patients and experimental animals [1,2,3,4,5,6,7,8,9,10,11,12,13,14,15]. The severity and prognosis of alkali burns varied.…”
Section: Introductionmentioning
confidence: 99%